Prediction of mental well-being based on emotional regulation, communication skills and problem solving ability in women with marital conflict - Vaghehdashti, Seyed Mohammadreza; Pourmolaie, Shayan; Ebrahimi Looyeh, Mozhgan (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of predicting mental well-being based on emotional regulation, communication skills and problem solving ability in women with marital conflict. Methods: The descriptive research method was of correlational type and the statistical population included all women with marital conflict who referred to counseling centers in Tunkabon city between May and November 2022. Using available sampling, 180 women who had marital conflict and scored higher in the marital conflict questionnaire were selected as a statistical sample. The tools used in the research were: Barati and Sanai Marital Conflict Questionnaire (1996), Ryff Mental Well-Being Scale Short Form (1985), Gross and John Emotional Regulation Scale (2003), Mathson Communication Skills Questionnaire (1983) and Ability Questionnaire Solving Heppner’s problem (1988). Data analysis was done by Pearson correlation and stepwise regression. Results: The results showed that the relationship between emotional regulation variables, communication skills and problem solving ability with mental well-being is positive and significant at the level of 0.01. In order to determine the best predictor of mental well-being among the predictor variables of emotional regulation, communication skills and problem solving ability, a step-by-step regression model was used. The results showed that the variable of communication skills has been able to justify 53.9% of the variance of mental well-being, and by adding the variable of emotional order to the variable of communication skills in the second model, it has added 2% of the variance of mental well-being, and the variables of communication skills and order Emotional seeking has been able to explain about 55.3% of the variance of mental well-being variable. Conclusion: It can be concluded that mental well-being can be predicted based on emotional regulation, communication skills and problem solving ability in women with marital conflict.